User perception of location based services - Aiginitis, Jason (2013)
Location based services are nowadays embedded in most services and devices that individuals use throughout their day. Those location based services are used to get directions, information for their location or even get informed about events. A lot of studies have been conducted focusing on the adaptation of location based services or the experience the users have while using those services. During this research the understanding of location based services and if the users understand the possible trade-offs that exist was researched. Since those services are embedded in modern technology by studying and analysing the beliefs and understanding the users have around those services can assist in better understanding the real user needs and assist in bettering those services. In order to achieve the goals of the study, fieldwork was conducted in the form of interviews. A total of twelve participants were recruited to participate in the study and scenario driven interviews were conducted in order to collect the appropriate data for analysis. The analysis of the data resulted in four main themes that best describe the user beliefs. Those four themes are "Positive View of Location Based Services", "Accepting and expecting no Privacy", "Having difficulties accessing information about the location based services" and "Wanting to change how the services work" with the majority of the participants having a positive view of location based services. Those themes are analysed and discussed and the impact they can have in means of design and user acceptance levels is also presented later during this study. The limitations that existed during the research are also discussed along with the possible future work at the discussion part of the study.